1969
DOI: 10.1159/000196929
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the Secretion of Acid, Pepsin, Sulfated Polysaccharides and Glycoproteins by the Dog Fundic Mucosa

Abstract: The secretion of acid, pepsin, chondroitin sulfate and glycoproteins from mucus have been studied in four Heidenhain pouch dogs, under basal condition and during stimulation with histamine, a gastrin- like pentapeptide and a cholinergic drug. Histamine and the gastrin analogue stimulate acid and, to a lesser extent, pepsin secretion, and they inhibit mucus secretion; cholinergic stimulation increases the output of acid, chondroitin sulfate, pepsin and glycoproteins of the mucus. No qualitative changes in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1971
1971
1979
1979

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Thus, this secretion was primarely stimulated by the gastrointestinal hormones. Previous studies have shown that the mucous secretion was poorly stimulated or even inhibited in these circomstances [13], Conversely, the combined histaminic and cholinergic stimulation used in our study stimulates the mucous secretion. Thus, this latter study explores the capacity of mucous cells to secrete glycoproteins, while G oksen and Hardy study refers to the secretion in response to a hormonal stimulation.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Thus, this secretion was primarely stimulated by the gastrointestinal hormones. Previous studies have shown that the mucous secretion was poorly stimulated or even inhibited in these circomstances [13], Conversely, the combined histaminic and cholinergic stimulation used in our study stimulates the mucous secretion. Thus, this latter study explores the capacity of mucous cells to secrete glycoproteins, while G oksen and Hardy study refers to the secretion in response to a hormonal stimulation.…”
Section: Discussioncontrasting
confidence: 64%
“…The latter constitute the visible mucus, and only a small fraction of this visible mucus dissolves in the gastric juice [5], Under fasting conditions, mucous cells of the surface secrete continuously their glycoproteins but the acid, pepsin and chondro'ftin sulfate outputs are low. Stimulation by hista mine or gastrin increases acid but decreases mucus secretion, while during a combined stimulation by gastrin and a vagoniimetic, or histamine and a vagomimetic, peptic, parietal and mucous cells were all strongly stimulated [13]. Thus, such a combined stimulation was used to study the effects of corticosteroids on the activity of the different cells of the fundic mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ley et al (34) reported that gastrin-like pentapeptide induced 'a drop of the output of both total and acidic glycoproteins of the mucus', during the first hour of gastrin-like stimulation of canine stomachs. Thus, the difference between fasting and pentagastrin-stimulated gastric 'control' collections, regarding gastric mucus, can be explained by the 'acute' action of pentagastrin.…”
Section: Pentagastrin-stimulated Secretionmentioning
confidence: 99%